Evaluation of Vortex Generators in the Heat Transfer Improvement of Airflow through an In-Line Heated Tube Arrangement - Syaiful; Tri Wahyuni; Bambang Yunianto; Nazaruddin Sinaga (Fluids, 2021)
Improving heat transfer from surface to airflow is a current research concern for enhancing energy efficiency. The use of vortex generators for improving heat transfer from the surface to the airflow is very effective. Therefore, this study focuses on applying flat and concave vortex generators with and without holes in order to improve heat transfer. In this study, the number of pairs of vortex generators was varied from one to three pairs at a certain angle of attack for various forms of vortex generators. The airflow velocity through the duct was varied in the range of 0.4 to 2.0 m/s at 0.2 m/s intervals. From the investigation results, we observed that the highest thermal performance was found with the use of concave delta winglets without holes for various pairs of vortex generators in terms of the overall Reynolds number. The highest thermal enhancement factor was found to be around 1.42 at a Reynolds number of approximately 9000. From this study, it was also shown that the lowest cost–benefit ratio was about 1.75 at a Reynolds number of approximately 3500 for three pairs of vortex generators.